HIV/Std Risk Behaviors and Perceptions Among Rural-to-Urban Migrants in China - Li, Xiaoming (2004)
Data from 2,153 sexually active rural-to-urban migrants in China were analyzed to examine the relationship between the movement of rural-to-urban migration and increased HIV/STD (sexually transmitted disease) risk and the applicability of constructs of a Western-based theory of behavioral change to the study population. Measurements included migrant mobility, sexual risk, and the seven constructs of the protection motivation theory (PMT). Data in the current study suggest that high mobility among rural-to-urban migrants was associated with increased sexual risk. The PMT constructs are applicable in identifying perceptions and attitudes associated with sexual risk behaviors in this culturally distinct population. Increased sexual risk was associated with increased perceptions of extrinsic rewards, intrinsic rewards, and response cost. Also consistent with PMT, increased sexual risk was associated with perceptions of decreased severity, vulnerability, response efficacy, and self-efficacy. After controlling for a number of key confounding factors, all seven PMT constructs were associated with sexual risk in the manner posited by the theory. The association between mobility and sexual risk underscores the importance of effective HIV/STD prevention efforts among this vulnerable population. The social cognitive theories including the PMT may form a logical base for prevention intervention programs targeting rural-to-urban migrants in China.